VIRALITAS MEDIA SOSIAL DALAM KOMUNIKASI PARIWISATA DI LOMBOK - I Nengah Sudanayasa; I Ketut Putu Suardana (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2025)
Social media has become one of the main instruments in modern tourism communication. The phenomenon of virality creates new opportunities for destinations to gain rapid and widespread recognition, including on Lombok Island. However, behind these opportunities lie challenges such as unbalanced promotion, inadequate infrastructure, and the degradation of local cultural values. This article examines the issue of social media virality within the context of tourism communication in Lombok using a descriptive-qualitative approach through literature review and online media observation. The analysis shows that virality can strengthen destination images based on nature and culture, but it also poses risks of overexposure, value distortion, and dependence on short-term popularity. Therefore, the communication strategy for Lombok’s tourism should be directed toward ethical, participatory, and sustainable digital narratives.